PENGARUH MATERIAL RUANG PADA KENYAMANAN TERMAL RUANG MEMBATIK YANG MENGGUNAKAN SKYLIGHT STUDI KASUS: RUMAH BATIK KATURA, PLERED, CIREBON (The Effect of Space Material to Thermal Comfort of Batik Craftsperson Room with Skylight, Case Study: Batik Katura H - Dyah Nurwidyaningrum; Hidjan A.G; Rita Farida (Unika Soegijapranata Semarang, 2015)
Problem in using skylight for batik craftsperson is discomfort thermal that could bother batik craftsperson work. The skylight which used in the preliminary study was declared really effective for day lighting batik craftsperson work plane. This must be proved to comfort thermal problem. Questions in this research is how to solve discomfort thermal in the batik craftsperson space caused use skylight to natural light. The research method uses phenomenology and simulation ecotect program. Analysis about the condition of exixting show discomfort thermal because temperature is 32,79-35,01oC, still overheat than 27,1oC according to SNI 03-6572-2001. The analysis on alternatif 1 showed that the decrease in temperature 2,08oC be 30,01oC in June, but still too hot however these materials has have low U-value. Further analysis with the changes material properties, show reduced from the fist alternative 4,27oC become 28,52oC. Although this value has not yet reach 27,1oC l in SNI but thermal comfort could be achieved by air movement (mechanical fan) that can make people feel 2 oC temperature decrease from the real.